Toleransi Beragama Sebagai Pendekatan Misi Kristen Di Indonesia - Mangantibe, Veydy Yanto; Taliwuna, Mario Chlief (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2021)
This article discusses religious tolerance as a mission approach in Indonesia. Religious toleranceis not sufficient to respond only to the attitude of acknowledging and accepting reality indifferent beliefs. But it must also be understood as a way that is formed in the attitude of socialinteraction which recognizes that they must need other people in their differences. If not, thenthey will be faced with problems of personal beliefs driven by different teaching understandingswhich lead to conflict in the division of the nation. This article uses a qualitative approach with adescriptive analysis method. Religious tolerance is one of the "assets" for the creation of theUnitary State of the Republic of Indonesia (NKRI) in different ethnicities, cultures and religions.The religious tolerance that exists in Indonesian society is an opportunity to bring peace with theform of accommodation in the form of social interactions to avoid conflict which results in thedivision of the nation so that this has an impact on the peace and harmony of nations in differentbeliefs. This is also a form of mission approach with an attitude of faith that brings peace to God love in the midst of differences in ethnicity, culture and religious beliefs. Artikel ini membahas mengenai toleransi beragama sebagai pendekatan misi di Indoensia: Toleransi agama tidak cukup hanya direspon dengan sikap mengakui dan menerima kenyataan dalam keyakinan yang berbeda, namun harus dipahami sebagai cara yang terbentuk dalam sikap interaksi sosial yang mengakui bahwa mereka harus membuthkan orang lain dalam perbedaan, jika tidak maka akan diperhadapkan dengan maslah-masalah keyakinan pribadi yang didorong dengan pemahaman pengajaran yang berbeda yang mengikibatkan konflik pada perpecahan bangsa. Adapun artikel ini menggunakan pendekatan kualitatif dengan metode deskriptif analisis. Toleransi beragama adalah salah satu “modal” bagi terciptanya Negara Kesatuan Republik Indonesia (NKRI) dalam berbedaan suku, budaya dan agama. Sikap toleransi agama yang ada di tengah masyarakat Indonesia, merupakan kesempatan untuk membawa damai dengan bentuk akomodasi dalam wujud interkasi sosial demi menghidari konflik yang mengikibatkan pada perpecahan bangsa sehingga hal ini berdampak pada kedamaiaan dan kerhamonisan berbangsa dalam keyakinan yang berbeda. Tentunya ini juga sebagai bentuk pendekatan misi dengan sikap iman yang membawa damai kasih Allah ditengah-tengah perbedaan suku, budaya dan keyakinan agama.